MOTORS ACTIVIY FOR DISABLED CHILDREN FROM TWO TO SIX YEARS OF AGE (Fiep Bulletin - online, 2014)
From two to five years of age it's the so-called phase of basic movements of the children. In this phase the children learn important physics abilities like: coordination, time space orientation, balance, social contact, beat and differentiation. According to Gallahue (2003) this phase ensue a progression that can be subdivided in periods of training. The sequences of progression for periods of training initials and mature are same to lot of children. But the rate will depend as much of environmental factors as hereditary factors. In the disabled children usually the movement standards are developed slower, so the necessity of more stimulations. Then experiences can be determiner in the skills acquisition, doing the physical education an important rehabilitation instrument. This relate show the experience developed in the practice pedagogic of the Physic Education with heterogeneous group disabled children from two to five years of age in a Program of the Motor activity for disable - PROAMDE at the Universidade Federal do Amazonas (Federal University of Amazon). The objective it was to develop the motor skills of the children through their potentialities and to give opportunity to them to have social and affective relations. The activities developed with the children were of motors skills fundamentals: locomotion, manipulation and balance over some conception of psychometric for example corporal scheme, laterally, secular structural and spatial orientation. The skills were worked in agreement with possibility of each child, having the same objective with different strategies. As for contributions of the practice of physical education for children we notice significant improvements, like: development basic motor skills, emotional stability, social relations and corporal conscience. The participation of the parents in the activity revealed to be an important factor in the practice of activities, contributing for one better performance of the children in the activity. Therefore physical activity revealed to be essential for motor, cognitive and affective development of the disabled children.
Keywords: children; deficiency; motor skills